EFEKTIVITAS METODE SOSIODRAMA MATA PELAJARAN IPS KELAS VIII SMP NEGERI 13 SEMARANG - Susanti, Febri; ., Tukidi; Putri, Noviani Achmad (Universitas Negeri Semarang, 2019)
This research aims to determine the effectiveness of the use of sociodrama learning methods, the activities of learners, the response of learners, and the learning outcomes of learners after using the method of sociodrama learning IPS material changes in Indonesian society in the period of colonialism and the growth of nationality spirit. This research type is pre experiment with research design one group pre test post test. The population of this research is all students of class VIII SMP Negeri 13 Semarang. Data collection techniques used questionnaires, observations, tests, documentation. The result of the research shows: (1) effective sociodrama method used with effectiveness level 82,35% in very good criterion, (2) student activity in sociodrama learning included in good category with score 884, (3) student response in good category with score 63,91 and (4) learners' learning result increase, initially only 7 students reaching KKM value with average score 58,6 to 34 students reach KKM value with average value 87,06. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan metode pembelajaran sosiodrama, aktivitas peserta didik, respon peserta didik, dan hasil belajar peserta didik setelah menggunakan metode sosiodrama pada pembelajaran IPS materi Perubahan Masyarakat Indonesia pada Masa Penjajahan dan Tumbuhnya Semangat Kebangsaan. Jenis penelitian ini adalah pre eksperimen dengan desain penelitian one group pre test post test. Populasi penelitian ini adalah seluruh peserta didik kelas VIII SMP Negeri 13 Semarang. Teknik pengumpulan data menggunakan angket, observasi, tes, dokumentasi. Hasil penelitian menunjukkan: (1) metode sosiodrama efektif digunakan dengan tingkat efektivitas 82,35% dalam kriteria sangat baik, (2) aktivitas peserta didik dalam pembelajaran sosiodrama termasuk dalam kategori baik dengan skor 884, (3) respon peserta didik dalam kategori baik dengan skor 63,91 dan (4) hasil belajar peserta didik meningkat, awalnya hanya 7 peserta didik yang mencapai nilai KKM dengan rata-rata nilai 58,6 menjadi 34 peserta didik mencapai nilai KKM dengan rata-rata nilai 87,06.